2017
DOI: 10.1039/c6ta10693e
|View full text |Cite
|
Sign up to set email alerts
|

Unique allosteric effect-driven rapid adsorption of carbon dioxide in a newly designed ionogel [P4444][2-Op]@MCM-41 with excellent cyclic stability and loading-dependent capacity

Abstract: Allosteric effect-driven rapid stepwise CO2 adsorption of pyridine-containing anion functionalized ionic liquid [P4444][2-Op] confined into mesoporous silica MCM-41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The new peak at 1623 cm –1 is due to the stretching vibration of the C=O bond in the formation of carbamate after the absorption of CO 2 , and the results suggested that carbamate is formed between the basic nitrogen atom of DMAPA and CO 2 . 44 , 45 In addition, the appearance of a broader peak at 3135 cm –1 suggests the possible formation of zwitterions (NH 2 + COO – ) during the absorption of CO 2 . 46 As shown in Figure 7 b, the characteristic peaks of bicarbonate can be found at 1047 and 1157 cm –1 after capturing CO 2 with [DMAPAH][OAc]-EDA-H 2 O (20 wt %).…”
Section: Resultsmentioning
confidence: 99%
“…The new peak at 1623 cm –1 is due to the stretching vibration of the C=O bond in the formation of carbamate after the absorption of CO 2 , and the results suggested that carbamate is formed between the basic nitrogen atom of DMAPA and CO 2 . 44 , 45 In addition, the appearance of a broader peak at 3135 cm –1 suggests the possible formation of zwitterions (NH 2 + COO – ) during the absorption of CO 2 . 46 As shown in Figure 7 b, the characteristic peaks of bicarbonate can be found at 1047 and 1157 cm –1 after capturing CO 2 with [DMAPAH][OAc]-EDA-H 2 O (20 wt %).…”
Section: Resultsmentioning
confidence: 99%
“…and so on. 105,106 Mohamed et al 107 Compared with the encapsulated conventional ILs, the CO 2 capacity of the encapsulated functionalized ILs was further improved because of the chemical interaction. 111 The encapsulated acetate-based ILs and amino acid ILs (AA-ENILs) are also studied for CO 2 adsorption.…”
Section: Supported Il Adsorbentsmentioning
confidence: 99%
“…The N 2 sorption isotherms of MCM-41 nanoparticle are shown in Figure 3a. The adsorption and desorption isotherms of nitrogen on the MCM-41 nanoparticle displayed a type IV isotherm according to the IUPAC classification with two obvious hysteresis loops at relative pressures P/P 0 of 0.27-0.37 and 0.37-0.95, indicating the presence of uniform mesopores and particle-stacked macropores [60]. At the adsorption branch, the adsorbed amount of N 2 increased gradually with an increase in the relative pressure by multilayer adsorption [49].…”
Section: Characterization Of the Mcm-41 Mesoporous Silicamentioning
confidence: 99%